Perancangan UI/UX Aplikasi Perpustakaan Digital Berbasis Web dengan Pendekatan Metode Design Thinking - Risyda, Fitria; Gardenia, Yulisa; Awaluddin, Muryan (IKRA-ITH Informatika : Jurnal Komputer dan Informatika, 2024)
Today’s library management increasingly demands quality and professionalism so that the results can be utilized to the maximum extent possible by its users. The library on the Dirgantara Marsekal Suryadarma University campus already has a website-based digital library service. This service is aimed at students, lecturers and the general public who need book references. However, the services provided have limitations ranging from performance to user interface appearance. This research aims to develop a professional digital library at Dirgantara Marshal Suryadarma University. Designing the User Interface (UI) and User Experience (UX) using the Figma application with a good and intuitive Design Thinking method and can meet the expectations of the needs of Dirgantara Marsekal Suryadarma University library users. Testing using the Single Ease Question (SEQ) method to see the level of effectiveness, efficiency and user satisfaction with the UI/UX design prototype of the Digital Library Application that will be built. The test results show a value of 6.7 on a scale of 7, indicating that the UI/UX design of the application that has been designed is considered good and in accordance with user needs